The Joint Crisis Plan: A Powerful Tool to Promote Mental Health - Lequin, Pierre; Ferrari, Pascale; Suter, Caroline; Milovan, Marion; Besse, Christine; Silva, Benedetta; Golay, Philippe; Bonsack, Charles; Favrod, Jérôme (Frontiers in Psychiatry, 2021)
Purpose: The Joint Crisis Plan (JCP) has received growing interest in clinical and research settings. JCP is a type of psychiatric advance statement that describes how to recognize early signs of crisis and how to manage crises. The purpose of the present study, to our knowledge the first to be conducted on this topic in the French-speaking context and to include inpatients, was to describe the content of JCPs and how they are perceived by patients and the providers. Methods: The study used an exploratory, mixed, sequential method. Existing JCPs were retrospectively collected in several clinical contexts (hospital, community settings and sheltered accommodation). Based on their analyses, we conducted semi-structured interviews including some rating scales on the perception of the JCPS among patients and providers in these settings. For the qualitative analyses, content analyses were conducted with an hybrid approach using NVivo 12 software. Data were double-coded and discussed with a third researcher until agreement was reached. Results: One hundred eighty-four JCPs were collected retrospectively and 24 semi-structured interviews were conducted with 12 patients and 12 providers. No relatives could be included in the research process. The content of the studied JCPs was relevant and indicated that patients had good knowledge of themselves and their illness. Improvements in the quality of the therapeutic relationship, respect for patients’ choices and wishes and a greater sense of control of their illness were reported. The JCP was perceived as a very useful tool by patients and providers. Concerning JCPs limitations, lack of staff training, difficulties with the shared decision-making process and the poor availability of the JCPs when needed were reported. Conclusion: The study highlights that JCPs may be used with patients suffering from a large variety of psychiatric disorders in different care settings. The JCP is perceived as very useful by both patients and providers. The promising results of this study support the promotion of the wide use of JCPs with patients who have experienced crises. It is important to continue to research JCPs through impact studies that include family members.